Exploring traditional end-of-life beliefs, values, expectations, and practices among Chinese women living in England: Informing culturally safe care. Issue 5 (October 2015) - Fang, Mei Lan; Malcoe, Lorraine Halinka; Sixsmith, Judith; Wong, Louise Yuen Ming; Callender, Matthew
Abstract: Objective: This study explores the end-of-life (EoL) beliefs, values, practices, and expectations of a select group of harder-to-reach Chinese women living in England. Method: A cultural safety approach was undertaken to interpret 11 in-depth, semistructured interviews. Interviews were conducted in Mandarin and Cantonese. Transcripts were translated and back-translated by two researchers. Findings were analyzed using the technical analytical principles of grounded theory. Results: The key themes generated from our analysis include: acculturation; differential beliefs and norms in providing care: family versus health services; language and communication; Eastern versus Western spiritual practices and beliefs; and dying, death, and the hereafter. Significance of Results: End-of-life discussions can be part of an arduous, painful, and uncomfortable process, particularly for migrants living on the margins of society in a new cultural setting. For some Chinese people living in the United Kingdom, end-of-life care requires attention to acculturation, particularly Western versus Eastern beliefs on religion, spirituality, burial practices, and provision of care, and the availability of culturally specific care, all of which encompass issues related to gender. Stories of a purposive sample of Chinese women were viewed through a cultural safety lens to gain a deeper understanding of how social and cultural norms and expectations, in addition to the pressures of acculturation, impact gendered roles and responsibilities. The analysis revealed variations between/within Eastern and Western culture that resulted in pronounced, and oftentimes gendered, differences in EoL care expectations.